The Catholic Athlete #2: Me, an Idolater? - Aragón Vargas, Luis Fernando (2022)
This series of short reflections addresses athletes who profess the Christian faith, in an attempt to bring together sports and Christianity. I write as a Catholic, hence the title of the series. I trust, however, that athletes from other denominations may also find spiritual profit in these texts.